A crise dos vivos - Maria Helena da Cruz Coelho (Medievalista)
The second half of the fourteenth century witnessed economic hardship and social upheaval, resulting from epidemics that decimated populations, bad weather that caused famine, and wars that mobilised men and money and generated violence and destruction. This context of difficulties was experienced across the kingdom and locally and was therefore also felt in the city of Coimbra. In the upper part of the city – the Almedina – where the cathedral, its mother parish, was located, there were further tensions at play. In this area many powers coexisted, as it was home to the episcopal palace – the residence of many canons – the royal palace – the residence of many officials – as well as the Estudo Geral (the University) and the student quarter. The tension of those years even breached the walls of the cathedral itself, where the prelate Pedro Tenório and the canons of the chapter clashed. The awareness of this difficult atmosphere leads to the question: did this situation have repercussions on the religious life of the cathedral parish? Could this conflict have affected religious services and, specifically, the office of suffrage for the dead? These questions, as well as their answers, were prompted by the Livro das Capelas (lit., ‘Book of Chapels’), a composite manuscript drawn up in the 1370s, which details the existing chapels in the cathedral and the reforms to which they were subjected. The present article will focus on this small codex, describing its material aspects and analysing its content in search of answers to the proposed questions.